Parental Leave: Economic Incentives and Cultural Change - James Albrecht; Per-Anders Edin; Raquel Fernández; Jiwon Lee; Peter Skogman Thoursie; Susan Vroman (Institute of Labor Economics (IZA), 2024)
The distribution of parental leave uptake and childcare activities continues to conform to traditional gender roles. In 2002, with the goal of increasing gender equality, Sweden added a second "daddy month," i.e., an additional month of pay-related parental leave reserved exclusively for each parent. This policy increased men's parental leave uptake and decreased women's, thereby increasing men's share. To understand how various factors contributed to these outcomes, we develop and estimate a quantitative model of the household in which preferences towards parental leave respond to peer behavior. We distinguish households by the education of the parents and ask the model to match key features of the parental leave distribution before and after the reform by gender and household type (the parents' education). We find that changed incentives and, especially, changed social norms played an important role in generating these outcomes whereas changed wage parameters, including the future wage penalty associated with different lengths of parental leave uptake, were minor contributors. We then use our model to evaluate three counterfactual policies designed to increase men's share of parental leave and conclude that giving each parent a non-transferable endowment of parental leave or only paying for the length of time equally taken by each parent would both dramatically increase men's share whereas decreasing childcare costs has almost no effect.
Keywords: D10; J16; Z10; Z18; 330; parental leave; gender equality; childcare; culture